Crustacean bycatch from trawl fishery along north Tamil Nadu coast - Lakshmi Pillai, S.; Kizhakudan, Shoba Joe; Radhakrishnan, E. V.; Thirumilu, P. (Indian Journal of Fisheries, 2014)
Monthly and seasonal diversity of crustacean bycatch landed by trawl at the Chennai Fisheries Harbour from June 2005 to December 2009 is discussed. Seventy to eighty percent of the catch from the trawlers is made up of finfish, both commercial and non-commercial, and other resources like molluscs, crustaceans, and echinoderms. Crustaceans find a prominent place in the low value trawl bycatch that is usually landed in a state of decomposition and fetches only very low price. About 53% of the crustaceans in the bycatch are crabs, followed by stomatopods (23%) and shrimps (18%). A total of 64 crustacean species were recorded which include 37 species of brachyuran crabs, 1 species of anomuran crab, 16 species of shrimps, 2 species of lobsters and 8 species of stomatopods. Univariate and multivariate analysis was done for monthly and seasonal data sets. The Shannon-Weiner diversity index (H) ranged from 3.13 to 5.53 and species evenness (J) 0.92 to 0.99 for monthly data sets. Species richness (d) was highest (10.28) in July 2008. Seasonal diversity indices revealed Shannon-Weiner index to range from 4.76 to 5.59, species richness from 7.18 to 10.71 and Evenness Index (J) from 0.94 to 0.98. Cluster analysis showed that species assemblage co-occur in a parallel manner across months and seasons.